Mitochondrial Spare Respiratory Capacity Is Negatively Correlated with Nuclear Reprogramming Efficiency - Zhou, Yan; Al-Saaidi, Rasha Abdelkadhem; Fernandez-Guerra, Paula; Freude, Kristine K; Olsen, Rikke Katrine Jentoft; Jensen, Uffe Birk; Gregersen, Niels; Hyttel, Poul; Bolund, Lars; Aagaard, Lars; Bross, Peter; Luo, Yonglun (Stem cells and development, 2017)
Nuclear reprogramming efficiency has been shown to be highly variable among different types of somatic cells and different individuals, yet the underlying mechanism remains largely unknown. Several studies have shown that reprogramming of fibroblasts into induced pluripotent stem cells (iPSCs) requires remodeling of mitochondria and a metabolic shift from an oxidative state to a more glycolytic state. In this study, we evaluated the nuclear reprogramming efficiency in relation to mitochondrial bioenergetic parameters of fibroblasts from seven different human individuals. Using the Seahorse extracellular energy flux analyzer, we measured oxygen consumption rate (OCR) profiles of the cells, along with their nuclear reprogramming efficiency into iPSCs. Our results showed that fibroblasts with the lowest mitochondrial spare respiratory capacity (SRC) had the highest nuclear reprogramming efficiency, opposed to fibroblasts with the highest mitochondrial SRC, which showed lowest reprogramming efficiency. Furthermore, we found that targeted fluorescent tagging of endogenous genes (MYH6 and COL2A1) by CRISPR/Cas9-mediated homologous recombination was accompanied by an increase in the SRC level of the modified fibroblasts and impaired reprogramming efficiency. Our findings indicate a negative correlation between high mitochondrial SRC in somatic cells and low reprogramming efficiencies. This type of analysis potentially allows screening and predicting reprogramming efficiency before reprogramming, and further suggests that nuclear reprogramming might be improved by approaches that modulate the SRC.